Human sincerity factors for adaptation in software agents - Jaafar N.H.; Basir N.M.; Ahmad M.S.; Ahmad A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Software agents are known to assist humans in handling many complex systems. Currently, there are consciousness among researchers in software agents to continuously find ways to instill human traits in software agents' behaviors. Sincere behavior is one of the many noble human behaviors that one could consider to be adapted in software agents. Research show that sincerity culture within organizational communities helps organizations produce high quality services or products. To adapt humans' sincere behavior in software agents we conduct a study on the factors of humans' sincere behavior. The study entails a questionnaire survey based on 20 items that solicit self-evaluation of sincerity factors in the working environment. Factor analysis of the survey results shows that there are four factors that influence humans' sincere behavior in the work place: (1) passion in doing the job, (2) integrity towards the organization, (3) positive behavior, and (4) sacrifice. The findings would be useful for instilling human sincere behavior in software agents. © 2014 IEEE.